2005
DOI: 10.1128/aac.49.10.4128-4136.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of LBM415 (NVP PDF-713), a Novel Peptide Deformylase Inhibitor, for Treatment of Experimental Mycoplasma pneumoniae Pneumonia

Abstract: Mycoplasma pneumoniae is a major cause of community-acquired pneumonia. We evaluated the efficacy of LBM415, a novel peptide deformylase inhibitor antimicrobial agent, for the treatment of M. pneumoniae pneumonia in a mouse model. Eight-week-old BALB/c mice were intranasally inoculated once with 10 7 CFU of M. pneumoniae. Groups of mice were treated with LBM415 (50 mg/kg of body weight) or placebo subcutaneously daily for 13 days, starting 24 h after inoculation. Groups of mice were evaluated at the baseline; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
2
19
1
Order By: Relevance
“…A trend for a decrease in the proinflammatory cytokine TNF-␣ was also noted. In previous studies TNF-␣ has been directly associated with M. pneumoniae disease severity (12,13,17), and its lower concentrations in the BAL fluid may have contributed to the decreased histologic lung inflammation in the IL-12 KO mice. We also found a trend for a decrease in the anti-inflammatory cytokine IL-10 in the IL-12 KO mice; this could be explained by the fact that IL-10 is a known negative feedback regulator of IL-12 production from phagocytic and dendritic cells (50).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A trend for a decrease in the proinflammatory cytokine TNF-␣ was also noted. In previous studies TNF-␣ has been directly associated with M. pneumoniae disease severity (12,13,17), and its lower concentrations in the BAL fluid may have contributed to the decreased histologic lung inflammation in the IL-12 KO mice. We also found a trend for a decrease in the anti-inflammatory cytokine IL-10 in the IL-12 KO mice; this could be explained by the fact that IL-10 is a known negative feedback regulator of IL-12 production from phagocytic and dendritic cells (50).…”
Section: Discussionmentioning
confidence: 85%
“…IL-12 is a heterodimeric cytokine that is composed of two subunits (p40 and p35) and is produced by antigen-presenting cells (phagocytes and dendritic cells) and targets natural killer and the T cells inducing the production of gamma interferon (IFN-␥; the Th1 effector cytokine) (15,26,37). To evaluate the role of IL-12 in the pathogenesis of M. pneumoniae respiratory infection, we studied the effect of IL-12 deletion on airway dysfunction and inflammation using IL-12 (p35) knockout animals in our established murine model of M. pneumoniae pneumonia (12,13,17,18). …”
mentioning
confidence: 99%
“…Murine model studies have shown that M. pneumoniae infection induces a Th1 cytokine response in the lungs, manifested by elevated concentrations of IL-12 and IFN-␥ with associated airway obstruction (AO), airway hyperreactivity (AHR), and lung histologic inflammation (12,18). In a recent study utilizing IL-12 (p35) knockout (KO) mice in our established murine model of M. pneumoniae respiratory infection, we demonstrated, somewhat surprisingly, that the absence of IL-12 significantly reduced disease severity, as assessed by pulmonary histopathology, airway function, and quantitative cultures (36).To further study the role of IL-12, we evaluated the effect of intranasal IL-12 treatment on airway dysfunction and inflammation in our established murine model of M. pneumoniae pneumonia (12,13,18,19). …”
mentioning
confidence: 99%
“…To further study the role of IL-12, we evaluated the effect of intranasal IL-12 treatment on airway dysfunction and inflammation in our established murine model of M. pneumoniae pneumonia (12,13,18,19).…”
mentioning
confidence: 99%
“…In fact, removal of the formyl group of the first methionine is mandatory for its subsequent excision in the process of maturation of the polypeptide chain (7); therefore, PDFs are known to be essential for bacterial survival (8)(9)(10). Also, in pathogenic bacteria, PDF is a promising and wellexplored drug target (11)(12)(13).…”
mentioning
confidence: 99%